Optimizing marketing learning evaluation: Gamification with CIPP model at SMKN 1 Bandung - Dini Haryanti; Ayuni Hanifatunnisa; Zaki Mubarak; Angga Hadiapurwa (Curricula: Journal of Curriculum Development, 2023)
In this digital era, education is experiencing rapid growth, especially in the diversity of evaluations given to students, one of which is through gamification. This article explores optimizing learning evaluation through gamification in the CIPP (Context, Input, Process, Product) evaluation model in marketing education at SMKN 1 Bandung. The method used is descriptive quantitative research. Data collection is done through questionnaires and interviews. The data sources and subjects in this study are educators in the marketing subject at SMKN 1 Bandung and students majoring in Online Business and Marketing at SMKN 1 Bandung, with the object being the evaluation of marketing learning with the implementation of gamification in the CIPP model. The results of this study indicate that the learning evaluation process with gamification is well-received by students at SMKN 1 Bandung. Applying gamification in learning evaluation using the CIPP model enhances students' learning outcomes and creates a responsive, adaptive, and collaborative learning environment.